Studi Eksperimental Pengaruh Bilangan Reynolds pada Keefektifan dan Koefisien Tekanan Penukar Panas Berkas Pipa Eliptik Susunan Berseling - Budi Utomo Kukuh Widodo; Samsul Kamal; Suhanan .; I Made Suardjaja (Department of Mechanical Engineering, University of Udayana, 2012)
Experimental studies have been conducted on the elliptic tube bundle with a diameter equivalent to 0.75inches and the aspect ratio (AR) = 2.Tube bundle arranged alternate with 4-3-4 configuration and pitchlateral (SL) = 1.5 X axis major axis. Meanwhile pitch transverse (ST) varied 1.5 and 2 X minor axis. TheTesting was carried out in a subsonic wind tunnel with wind speeds of 1 m / s - 12.6 m / s resultingReynolds number Reb = 346-6904 and operating temperature 49 oC, 59 oC and 69 oC. Seven tubesinserted an electric heater produces uniform heat flux 3718 W/m2 - 3751 W/m2. The results show that theeffectiveness of the heat exchanger (Q / P) varied from 3799 to 15, decreases exponentially at lowReynolds number and tends to asymptotic at Reynolds number above 1000. Meanwhile, the valuepressure coefficient (?p/0.5?V2) with value 3.4-10 decreased continuously at low Reynolds numbers andasymptotic at high Reynolds number. In general, a bundle with a smaller ST has greater effectiveness andthe pressure coefficient ranges is wider. Changes in operating temperature conseqwenly no effect on theeffectiveness and the pressure coefficient at high Reynolds number.